As territorialidades das pequenas empresas de mineração no nordeste paraense: o caso do município de Capitão Poço (PA) - ROCHA, Danusa Di Paula Nascimento da (Universidade Federal do Pará, 2017)
This research aimed an analysis about the territoriality (practices and elements of the construction and areas control) who involving small-scale mining in the Pará northeastern, presenting as case study for minerals recovery for immediate use in civil construction (pebble and sand) in the Capitão Poço municipality. The analysis considered the socioeconomic, environmental and political attributes (including the legal aspects) that determine the valuation of mineral substances, and also aspects of the setup and organization of the territory, such the natural resource base (and even humans), which makes managing them and conflicts and associated impacts. Was chosen to organize the study employing partially the dialectical method. And, from a integrated geographical discussion to field observations and secondary data systematization of the institutions government obtained a cartographic production is related to the use and power over mineral resources. Thus, expected that the information produced provide subsidies to planning and management of mineral resources at regional and municipal level.